Statistical methods for engineers and scientists - Bethea, Robert M.; Duran, Benjamin S.;Boullion, Thomas L. (New York : Marcel Dekker, Inc., 1984)
This text is also useful for professional engineers and scientists especially because of its emphasis on regression, experimental design, analysis of variance, and computerized data reduction and interpretation.
Chapter 1. Introduction -- Chapter 2. Probability -- Chapter 3. Distributions -- Chapter 4. Descriptive statistics -- Chapter 5. Expected values and moments -- Chapter 6. Statistical inference: estimation -- Chapter 7. Statistical inference: hypothesis testing.
Includes index.
Keywords: MATHEMATIC STATISTICS